EXPLORING DETERMINANTS OF E-BUSINESS ADOPTION IN SMES: A SYSTEMATIC LITERATURE REVIEW (Jurnal Kemanusiaan, 2022)
Adoption of e-business is extremely a dominant strategy to survive, stay competitive and grow for businesses. However, empirical studies on e-business adoption in recent years have been scarce. The purpose of this paper is to review the paper systematically to explore determinants of e-business adoption in Small and Medium Enterprises (SMEs) of developing countries. E-business has substantial potential for SMEs in developed and developing countries alike. Nevertheless, to accelerate the shift from traditional business to e-business in developing countries faced many challenges in practical use and the issues have not been adequately addressed (Mkansi.M, 2020). In the scarcity of the extant literature, the direction of future work outlined. Guided by PRISMA technique (Moher et al., 2009), three online databases, Scopus, Web of Science and Springer Link Journal were deployed, resulting in 27 articles were included in the literature review and have been identified and diversified into various factors which related to the frequency of occurrence in many researches which apply technology-organization-environment (TOE) framework (Tornatzky and Fleisher, 1990). Further analysis of the studies under TOE framework revealed four significant themes: (1) Technological Context, (2) Environmental Context, (3) Organizational Context, and (4) Individual Context. The themes are combined into a proposed e-business adoption framework and recommendations are reconciled according to the proposed framework. This paper incorporates the insights of the determinants of e-business adoption in SMEs, it suggested pertinent issues for future research endeavors and serve as a portrait for more SMEs entrepreneurs in developing countries to adopt e-business to sustain, remain competitive and bloom in current covid-19 pandemic and hereafter.